Combat exposure, emotional and physical role limitations, and substance use among male United States Army Reserve and National Guard soldiers. - Hoopsick, R. A.; Vest, B. M.; Homish, D. L.; Homish, G. G. (Quality of Life Research, 2018)
Purpose: Combat-exposed soldiers are at an increased risk for health problems that diminish quality of life (QOL) and substance use. We explored the cross-sectional associations between combat exposure and two measures of QOL, and the effect of substance use on those associations.Methods: Data are from the baseline wave of Operation: SAFETY, an ongoing survey-based study of United States Army Reserve/National Guard (USAR/NG) soldiers and their partners. Our sample consisted of male USAR/NG soldiers with a history of deployment (N = 248). Limitations in usual activity due to physical and emotional problems were assessed using the 36-Item Short-Form Health Survey (SF-36).Results: Greater combat exposure was independently associated with limitations in usual activity due to physical (regression coefficient = -0.35, 95% CI -0.55 to -0.16, R 2 = 0.09; p < 0.01) and emotional (regression coefficient = -0.32, 95% CI -0.56 to -0.09, R 2 = 0.09; p < 0.01) problems. Combat exposure had a significant interaction with frequent heavy drinking on physical role limitations (regression coefficient = -0.65, 95% CI -1.18 to -0.12, R 2 = 0.12; p < 0.05) and emotional role limitations (regression coefficient = -0.83, 95% CI -1.46 to -0.19, R 2 = 0.12; p < 0.05). Combat exposure also had a significant interaction with lifetime non-medical use of prescription drugs on physical role limitations (regression coefficient = 0.81, 95% CI 0.18-1.45, R 2 = 0.11; p < 0.05).Conclusion: Combat is an unmodifiable risk factor for poor QOL among soldiers; however, frequent heavy drinking and non-medical use of prescription drugs modifies the relationship between combat exposure and QOL. Therefore, substance use is a potential point of intervention to improve QOL among soldiers.